The value of a peer - Ingo Eduard Isphording; Ulf Zölitz (University of Zurich, Department of Economics, 2020)
This paper introduces peer value-added, a new approach to quantify the total contribution of an individual peer to student performance. Peer value-added captures social spillovers irrespective of whether they are generated by observable or unobservable peer characteristics. Using data with repeated random assignment to university sections, we find that students significantly differ in their peer value-added. Peer value-added is a good out-of-sample predictor of performance spillovers in newly assigned student-peer pairs. Yet, students' own past performance and other observable characteristics are poor predictors of peer value-added. Peer value-added increases after exposure to better peers, and valuable peers are substitutes for low-quality teachers.
Keywords: I21; I24; J24; 330; peer effects; peer value-added; peer capital; spillovers